Ta có:\(1990^{10}+1990^9\)
\(=1990^9.1990+1990^9\)
\(=1990^9.\left(1990+1\right)\)
\(=1990^9.1991< 1991^9.1991=1991^{10}\)
\(\Rightarrow1990^{10}+1990^9< 1991^{10}\)
199010 + 19909 và 199110 = (1990.1990.......1990)+(1990.1990.....1990) và (1991.1991.....1991) Vì có 10 số 1991 nhân nhau nên nó lớn hơn 10 số 1990 và 10 số 1991 nhân nhau lớn hơn 9 số 1990 nhân nhau
199110 >199010
199110>19909
Ta có: \(1990^{10}+1990^9=1990^9.1990+1990.1\)
\(=1990^9.\left(1990+1\right)\)
\(=1990^9+1991\)
\(1991^{10}=1991^9.1991\)
Vì \(1990^9< 1991^9.\)Suy ra\(1990^9.1991< 1991^9.1991\)
Nên\(1990^{10}+1990^9< 1991^{10}\)